Individual factors that predict customer-orientation behaviour of Malaysian life insurance agents - Mohd Noor, Nor Azila; Muhamad, Azli (Universiti Kebangsaan Malaysia, 2005)
The topic of customer-orientation has increasingly attracted interest in both academic marketing research and practice.One major factor which has been increasingly discussed as an important driver of a salespeople’s customerorientation is individual factor.In this study we examine the influence of three individual factors; namely, organizational commitment, self-monitoring and intrinsic motivation on salespeople customer-orientation behaviour.Data gathered from 445 life insurance agents were used to test the hypothesized relationship.The results suggest that organizational commitment and intrinsic motivation positively influence salespeople to perform customer-orientation behaviour in their selling activities.Self-monitoring however, was found to be unrelated to the adoption of customer orientation behaviour.The academic and managerial implications of these findings are then discussed.